The Relationship between Social Support and Well-Being of Parents of Children with Special Needs - Katsiotas, Nikki Joan; Ding, Yi; Alfonso, Vincent C.; Zusho, Akane; Zhang, Anqi; Shen, Yangqian (Advances in Social Sciences Research Journal, 2026)
The purpose of the study was to conduct an exploratory investigation to determine how to best conceptualize social support for parents of children with special needs and to identify which dimensions of support may be most relevant for interventions. An exploratory factor analysis was conducted to investigate the factor structure of perceived social support. The results indicated that tangible support, information support, emotional support, and negative social contact each represented distinct dimensions of social support. Regression analyses were then conducted to determine which dimensions were most relevant to well-being. The results indicated that negative social contact and emotional support had significant direct effects on the well-being variables and that emotional support had a significant moderating effect on the relationship between stress and negative affect. Overall, the results suggest that social support for parents of children with special needs is best conceptualized as a multidimensional construct.